2021
DOI: 10.3389/fphys.2021.706032
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing, Expression, and Functional Analyses of Four Genes Related to Fatty Acid Biosynthesis During the Diapause Process in the Female Ladybird, Coccinella septempunctata L.

Abstract: The ladybird Coccinella septempunctata L., a predatory insect, serves as an excellent biological control agent against common agricultural pests. It undergoes a diapause phenomenon, during which a large amount of fat accumulates in the abdomen. A comprehensive analysis of this lipid accumulation can reveal the molecular mechanisms underlying diapause regulation, which can be exploited to improve the shipping and transport of the insect for agricultural applications. In this study, we compared the transcriptome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Our transcriptome and proteome results showed that ACC , which converts sugar to fat, and LSD1 and LSD2 , which are involved in lipid accumulation, showed increased expression in diapause females of C. nipponensis (Figures 6 and S4). 2,60–62 Similarly, expression of ACC was higher in diapause female adults of Coccinella septempunctata than in non‐diapause female adults 61 . Knockdown of ACC led to decreased lipid content in diapause female adults of C. septempunctata 61 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our transcriptome and proteome results showed that ACC , which converts sugar to fat, and LSD1 and LSD2 , which are involved in lipid accumulation, showed increased expression in diapause females of C. nipponensis (Figures 6 and S4). 2,60–62 Similarly, expression of ACC was higher in diapause female adults of Coccinella septempunctata than in non‐diapause female adults 61 . Knockdown of ACC led to decreased lipid content in diapause female adults of C. septempunctata 61 .…”
Section: Discussionmentioning
confidence: 96%
“… 2,60–62 Similarly, expression of ACC was higher in diapause female adults of Coccinella septempunctata than in non‐diapause female adults 61 . Knockdown of ACC led to decreased lipid content in diapause female adults of C. septempunctata 61 . LSD2 transcript levels were significantly higher in diapause females of Aedes albopictus and L. decemlineata than in non‐diapause females 60,63 .…”
Section: Discussionmentioning
confidence: 96%